1997
DOI: 10.1128/jvi.71.6.4782-4790.1997
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting of human cells by a chimeric adenovirus vector containing a modified fiber protein

Abstract: The adenovirus fiber protein is responsible for attachment of the virion to unidentified cell surface receptors. There are at least two distinct adenovirus fiber receptors which interact with the group B (Ad3) and group C (Ad5) adenoviruses. We have previously shown by using expressed adenovirus fiber proteins that it is possible to change the specificity of the fiber protein by exchanging the head domain with another serotype which recognizes a different receptor (S. C. Stevenson et al., J. Virol. 69:2850-285… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…This confirmed that an 'Ad5' vector possessing Ad3 tropism had been produced. A similar strategy was reported by Stevenson and colleagues 38 who also demonstrated differences in the gene transfer efficiency of various cell lines depending on whether wild-type or chimeric fiber vectors were used. 38 After the initial proof of principle, incorporation of specific targeting ligands was investigated.…”
Section: Genetic Retargetingmentioning
confidence: 70%
“…This confirmed that an 'Ad5' vector possessing Ad3 tropism had been produced. A similar strategy was reported by Stevenson and colleagues 38 who also demonstrated differences in the gene transfer efficiency of various cell lines depending on whether wild-type or chimeric fiber vectors were used. 38 After the initial proof of principle, incorporation of specific targeting ligands was investigated.…”
Section: Genetic Retargetingmentioning
confidence: 70%
“…Similarly, replica-tion-competent or replication-defective viral vectors derived from Ad7 have been used for vaccine strategies (Abrahamsen et al, 1997;Lubeck et al, 1989;Nan et al, 2003). An extended tropism was also demonstrated for fiber swapped Ad vectors containing fibers of species B viruses such as Ad3 (Kanerva et al, 2002;Stevenson et al, 1997;Von Seggern et al, 2000), Ad11 (Stecher et al, 2001), and Ad35 Havenga et al, 2002;Knaan-Shanzer et al, 2001;Rea et al, 2001;Shayakhmetov et al, 2000;Yotnda et al, 2001). To generate a tool for characterization of host cell -Ad3 interactions, we constructed a recombinant E1-deleted Ad3 vector expressing eGFP using the bacterial artificial chromosome (BAC) strategy, and we report here the complete nucleotide sequence of serotype Ad3 (GB) (GenBank accession no.…”
Section: Introductionmentioning
confidence: 98%
“…The adenovirus fiber protein is a major determinant of adenovirus tropism (Gall et al, 1996;Stevenson et al, 1997). The fiber protein extends from the capsid and mediates viral binding to the cell surface by binding to cell surface receptors (Philipson et al, 1968).…”
Section: Introductionmentioning
confidence: 99%